Электротермическое воздействие импульса тока искусственной молнии на пожароустойчивость покрытия наружной кровли из нержавеющей стали - Рудаков, Сергей Валерьевич; Рудаков, И. С. (Національний університет цивільного захисту України, 2018)
The results of numerical and experimental assessment of the electro-thermal resistance of thin-walled covering of an exterior roof of high-rise constructions of stainless steel to the direct influence of the impulse of current of artificial lightning. It is shown that the specified impulse lightning current causes a local surface thermal damage of the investigated steel coating when the radius of the damage zone, not more than 30 mm and the depth of penetration of its wall of not more than 50 microns., that can produce a fire insulating materials
Electrothermal Effects of the Impulse of Current of Artificial Lightning on the Fire Resistance of the Outer Coating of the Roof with Stainless Steel
Keywords: наружная кровля; покрытия; пожароустойчивость; искусственные молнии; электротермическое воздействие; нержавеющая сталь; металлические кровельные системы; электротермическая стойкость; листовые покрытия; нормированный апериодический импульс